2023
DOI: 10.13189/ujar.2023.110207
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Characteristics of Broiler Chickens (Gallus gallus domesticus) Supplemented with Turmeric Rhizome Powder (Curcuma longa)

Abstract: Curcumin is an active ingredient in turmeric known to serve as an antioxidant, anti-mutagen, and anti-carcinogen. A hundred broiler chickens were subjected to a feeding experiment subdivided into five treatments (0, 2.5, 5.0, 7.5, and 10 grams of turmeric rhizome powder per kilogram of basal diet) at four replications in a randomized complete block design and brooded at 15 days and 30 days under the feed trial to determine the effect of turmeric rhizome powder (TRP) on the visceral organs of broiler chickens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…However, it was reported that the taste quality of broiler meat fed with mushrooms was lower compared with the rest of the treatments. Camay [ 4 ] reported that the texture quality of broiler meat fed with 5 g P. ostreatus per kg of feed showed the lowest sensory rating, and it varies with the inclusion rate (10 g and 25 g). Similarly, the lowest general acceptability rating was observed in the broilers fed 5 g P. ostreatus .…”
Section: Meat Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, it was reported that the taste quality of broiler meat fed with mushrooms was lower compared with the rest of the treatments. Camay [ 4 ] reported that the texture quality of broiler meat fed with 5 g P. ostreatus per kg of feed showed the lowest sensory rating, and it varies with the inclusion rate (10 g and 25 g). Similarly, the lowest general acceptability rating was observed in the broilers fed 5 g P. ostreatus .…”
Section: Meat Qualitymentioning
confidence: 99%
“…The microscopic spores produced by the pores or gills help the fungus spread across the ground or its occupant surface [ 3 ]. Mushrooms have nutritional and medicinal value, but in recent times, they have become more significant because of their nutraceutical value [ 4 ]. Several mushrooms have demonstrated bioactivity properties such as antifungal, antibacterial, antiparasitic, antiviral, antioxidant, anti-inflammatory, anti-proliferative, cytotoxic anticancer, antitumor, hepatoprotective, hypocholesterolemic, antidiabetic, anticoagulant, and anti-HIV properties [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation